Forced and natural ventilation of a room with a combined solar chimney and Earth - to - Air Heat Exchanger system. Issue 1 (March 2021) - Nguyen, V T; Nguyen, Y Q
Abstract: In this study, a passive ventilation and cooling technique which is widely used in sustainable building designs was investigated by a numerical simulation based on computational fluid dynamics (CFD). A system of a solar chimney (SC) and an Earth-to-Air Heat Exchanger (EAHE) is able to ensure thermal comfort in a house by generating an air flow which is induced by the thermal effect. The solar chimney drew ambient air (at 35°C) through the inlet of EAHE; the air flow was cooled by a lower temperature of the underground pipes (at 20°C) before circulating inside the house and leaving through the outlet of the solar chimney. Both the openings of the system were exposed to the atmosphere, and the atmospheric pressure was set at the inlet of the EAHE pipe and the outlet of the solar chimney. The performance of this ventilation and cooling system was analyzed under effects of design parameters, including the gap of the chimney, the diameter and length of the EAHE pipe as well as the solar heat flux applied on the wall of the air channel of the chimney. The results of the assessed parameters, such as temperature inside the house, show that the indoor temperature was reduced to 25°C and 26°C, respectively for the forced ventilation case of 0.2 m/s and natural ventilation case in the configuration with the EAHE pipe length of 11m. The coupled solar chimney and EAHE system can achieve the thermal comfort conditions for both cases of natural and forced ventilation.